THE PERMEABILITY OF THE SCLERAL TISSUE FOR ULTRAVIOLET A IN THE EXPERIMENT - M. M. Bikbov; V. K. Surkova; E. L. Usubov; S. V. Kharitonov; A. B. Simonov; M. N. Astrelin (Oftalʹmologiâ, 2017)
Purpose: to evaluate the permeability of the scleral tissue for ultraviolet A (UVA).Materials and Methods. The study was conducted on 15 cadaver porcine eyes. Rectangular scleral flap 12*15 mm was cut out from each eyeball. The thickness of the sample was measured with a digital caliper. The outer surface of the scleral flap was irradiated with ultraviolet A. A sensor of the UV-radiometer was placed under the sample. It measured the UVA irradiance passing through the sclera. The absorption coefficient of ultraviolet A by the sclera was calculated from the formula derived from the Bouguer-Lambert Beer law: , where  E0 — the absorption coefficient, mm-1;  — irradiance of the transmitted light, mW/cm2; I0 — irradiance of the received light, mW/cm2; — thickness of the sclera, mm.Results. The absorption coefficient of ultraviolet A by the sclera was 4,91±0,43 mm-1. According literature the threshold damaging radiation for retina is 7.7 J/cm2. Substituting these values in the converted formula of the Bouguer-Lambert-Beer law, we can derive an equation for calculating the threshold UVA irradiation dose of the sclera: , where 0 — the threshold UVA irradiation dose of the sclera, J/cm2;  — the base of the natural logarithm; — thickness of the sclera, mm.Conclusion. The absorption coefficient of ultraviolet A by the cadaver porcine sclera is 4,91±0,43 mm-1. The derived formula of the threshold UVA irradiation dose of the sclera calculating allows to avoid the threatening for the retina procedure parameters in the performance of the scleral crosslinking with riboflavin/UVA.